Magnetic and Dyed Microcapsules From the Spores of Clubmoss - Cai, Wen; Bradbury, Charles; Cowling, Stephen; Goodby, John (Frontiers in Physics, 2022)
In this article we describe the preparation of microcapsules derived from spores of clubmoss (lycopodium clavatum) that are composed of protein-free, non-allergenic, and porous sporopollenin, which is often described as nature’s most robust polymeric system. We describe the adsorption of magnetic materials onto the exterior surfaces of the empty microcapsules and the incorporation of dyes, thereby producing coloured, monodispersed, bifunctional particles/vehicles of 25 microns in size that can respond to magnetic fields.